Fgr contributes to hemorrhage-induced thalamic pain by activating NF-κB/ERK1/2 pathways - Huang, Tianfeng (JCI Insight, 2020)
Thalamic pain, a type of central poststroke pain, frequently occurs following ischemia/hemorrhage in the thalamus. Current treatment of this disorder is often ineffective, at least in part due to largely unknown mechanisms that underlie thalamic pain genesis. Here, we report that hemorrhage caused by microinjection of type IV collagenase or autologous whole blood into unilateral ventral posterior lateral nucleus and ventral posterior medial nucleus of the thalamus increased the expression of Fgr, a member of the Src family nonreceptor tyrosine kinases, at both mRNA and protein levels in thalamic microglia. Pharmacological inhibition or genetic knockdown of thalamic Fgr attenuated the hemorrhage-induced thalamic injury on the ipsilateral side and the development and maintenance of mechanical, heat, and cold pain hypersensitivities on the contralateral side. Mechanistically, the increased Fgr participated in hemorrhage-induced microglial activation and subsequent production of TNF-α likely through activation of both NF-κB and ERK1/2 pathways in thalamic microglia. Our findings suggest that Fgr is a key player in thalamic pain and a potential target for the therapeutic management of this disorder.